PEMBUATAN MEDIA SLIDE SUARA UNTUK MATA PELAJARAN SEJARAH SMU - Rokhman, M Nur; Murdyastomo, HY. Agus (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
History  teachers  at senior  high schools  in the Kulon  Progo  Regency were  given  training  in making  audio-slide  media  with the  objectives   of im proving   the  quality   of  history   teaching   at  those  schools,   enabling   those teachers   to  acquire   via  given  lectures,  demonstrations,    and  exercises   the knowledge  and skills  in making  audio-slide  media,  and arousing  the creativ ity that would  enable  them  and make them willing to make  their  own audio-slide media.  An  attempt  to solve  the problem  of achieving  those  objectives was made  by means  of lectures  about the importance  of media  in general  in teaching-learning    activities,   lectures  about  making  audio-slide   media,  train ing in making  such  media,  practice  in making  them,  and  evaluation   of the results.The  activities   in carrying  out  that  public  service  involving   applied science   and  technology    were   conducted   through   lectures   followed   with question-and-answer    sessions,  lectures  followed  with demonstrations,   train ing and tutorials,  and practice  in making  audio-slide  media.The  activities   resulted  in the participants  gaining  knowledge,   skills, and  experience   in making  such  media.  Coordination   with  the  MGMP,  the organization   developing   working  teachers'   expertise,  ran  well;  the  training was  held  at  a  state  senior  high,  SMU  N  I  Sentolo,  on  Wednesdays    (the MGMP  day  for senior  high  history  teachers).  Twenty  teachers  participated and two  sets  of audio-slide   media  for Grade-l   class  materials   with  two  to pics: historical sources, evidence, and facts and historical tradition in Indo nesian society before the coming of writing with an instrumental   version  of the patriotic  marching  song Halo Halo Bandung as the opening  and closing musical  background   resulted  from the activities.  Two other  topics  would  be developed   by  groups   not  yet  succeeding   in  making   such  media   and  the MGMP   for  senior  high  history   teachers   hope  that  similar   public   service would be held involving  other topics or materials.Keywords: science and technology, audio media, teaching media